The Role of Social Security in Household Decisions: Var Estimates of Saving and Fertility Behaviour in Germany - Alessandro Cigno; Luca Casolaro; Furio C. Rosati (Center for Economic Studies and ifo Institute (CESifo), 2000)
Estimating saving and fertility simultaneously by the VAR method, we find that social security cover has a positive effect on household saving, and a negative effect on fertility. In Germany, as in other countries where the hypothesis was tested, social security is thus good for growth. A possible explanation for this unconventional finding is that compulsory saving in the form of pension contributions tends to displace intra-family transfers, rather than asset formation. However, the negative effect of social security on fertility tends to erode the system's own contributory base, because it reduces the number of future contributors. That is one of the reasons why, in Germany as elsewhere, pay-as-you-go pension systems tend to be financially unstable. To some extent, this is counteracted by child-related benefits, which tend to encourage fertility, but the effect appears to be weak.
Keywords: 330